Efektivitas Game Edukatif Sebagai Media Pembelajaran untuk Meningkatkan Literasi Budaya dan Numerasi Siswa Sekolah Dasar - Nur Aulia Rahmawati; Alfi Laila; Novia Rosyidatud Dalalah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to examine the effectiveness of educational games as learning media to enhance cultural literacy and numeracy among elementary school students through a Systematic Literature Review (SLR). The review followed the PRISMA 2020 protocol and identified 21 studies that met the inclusion criteria. Using the PREC framework, the analysis mapped the population, research context, empirical evidence, and comparisons across studies. The results indicate that educational games consistently improve numeracy skills, including number sense, arithmetic operations, and problem-solving abilities. Furthermore, the integration of local cultural elements into game design enhances cultural literacy by strengthening students’ understanding of cultural symbols, local values, and contextual learning experiences. The findings also reveal several factors influencing successful implementation, such as game design quality, teacher readiness, technological infrastructure, and institutional support. Challenges arise from limited teacher competence, inadequate facilities, and technological disparities among regions. Overall, educational games demonstrate strong effectiveness as interactive and contextual learning tools aligned with 21st-century education demands.